Thermodynamic and economic assessments of gas turbine inlet air-cooling by evaporative technique - Erdem, Hasan Hueseyin (INDERSCIENCE ENTERPRISES LTD, 2009)
In this study, the effects of gas turbine inlet air-cooling by evaporative technique on work output and thermal end exergy efficiency were analysed. These analyses are performed with the use of per unit volumetric flow, which is fixed regardless of atmospheric air conditions. In addition, a simple and effective model is developed for the economic analysis of evaporative cooling. As a case study, the payback periods of two different gas turbine models are calculated for eight different regions in Turkey. Depending on the technical, economic and environmental conditions, evaporative cooling may be suitable for the regions considered.
Keywords: gas turbine; evaporative cooling; cost analysis; thermal efficiency; exergy efficiency; PERFORMANCE; CYCLE; SYSTEMS; Thermodynamics; Energy & Fuels